Faktor Tingginya Partisipasi Politik Masyarakat Desa Sidetapa Pada Pemilu Legislatif Tahun 2014 - Mastini, Komang; Bandiyah, Bandiyah; Azhar, Muhammad Ali (Jurnal Nawala Politika, 2017)
Village Sidetapa is the Village of Bali Aga in order to level of political participation which is always high when the activities of the election. The research to see high participation factors of villagers Sidetapa in legislative elections year 2014. As a frame research, a theory that used in this research is a theory political participation. Methods used in this study is descriptive qualitative. These findings this research is: First, the mobilization the through Buldog by the potential legislative. Second, there are relation actor political and Buldog, and Third is the punishment or rewards. Based on the findings, the conclusion of political mobilization, the relation and the punishment or reward affecting community choices in the election influence on the winning the legislature and high political participation of villagers Sidetapa community.   Keywords: Political Participation, Mobilization of Political, The Local Powerfull, and Sidetapa village.